Pemasaran Berkelanjutan pada Usaha Olahraga Biliar: Media Sosial untuk Capai Netralitas Karbon - Sari, Ratna Deli; Siahaan, Petrus Kennedi (LPPM Universitas Sangga Buana, 2025)
Sustainability-focused marketing approaches are gaining increasing attention, particularly in supporting micro, small, and medium enterprises (MSMEs) committed to achieving carbon neutrality as part of collective responsibility towards climate change. Social media has become an effective strategic tool to efficiently reach a broader audience, with platforms like Instagram, Facebook, and TikTok providing opportunities to strengthen emotional connections, enhance customer loyalty, and support sustainability programs.This study focuses on PT Lucky Shot, an MSME in the billiard sports sector, which faces challenges in maintaining competitiveness in a dynamic market while adhering to its commitment to environmental sustainability. The research adopts a qualitative descriptive approach to analyze the application of environmentally focused marketing strategies through social media at PT Lucky Shot. Data were collected through literature reviews and direct observation of the company’s social media marketing activities.The study provides in-depth insights into patterns, challenges, and opportunities in integrating sustainability strategies with social media marketing. It is designed to develop an applicable sustainability-based marketing model aimed at supporting the achievement of carbon neutrality targets while enhancing the competitiveness and reputation of MSMEs